Importance of urine sodium dithionite test in paraquat poisoning: a case study - Ingale, Pramod W.; Shelke, Sudarshan N.; Sundharan, Shimi; Raul, Namrata M. (International Journal of Research in Medical Sciences, 2017)
Suicidal tendencies are one of the major social problems worldwide. It is equally seen in Indian population. Organo-phosphorus compounds are usually preferred because of their easy availability. Paraquat is one of the lesser known herbicide agent, which is not an OP compound. It is highly toxic and causes damage to the lungs, liver and kidneys. Occurrence of paraquat poisoning is rare, but has very high mortality rate. Here we report one such case which was earlier misdiagnosed as organo-phosphorus poisoning, but diagnosed later by qualitative urine sodium dithionite test. It is a simple test for early diagnosis of paraquat poisoning. It is recommended to performing this test in all suspected cases of oral poisoning.